REPRESENTASI KONFLIK WONG CILIK DALAM NOVEL BILA MALAM BERTAMBAH MALAM KARYA PUTU WIJAYA DAN NOVEL PENGAKUAN PARIYEM KARYA LINUS SURYADI AG: KAJIAN INTERTEKSTUAL - Sari, Ratna; Juita, Novia; Nst., Muhammad Ismail (Jurnal Bahasa dan Sastra, 2018)
The type of this research is qualitative research using descriptive analysis methods. This research data is a text in from of the words, phrases, clauses, sentences and discourse which represents conflicts of wong cilik, in the form of personal and between classes conflict in both novels. It is also looking for differences and similarities of the conflicts, and explaining the novel Bila Malam Bertambah Malam by Putu Wijaya as hypogram of novel Pengakuan Pariyem by Linus Suryadi AG. The results of the study are First, the conflict of wong cilik in novel Bila Malam Bertambah Malam there are nine conflicts of wong cilik, devided into six personal conflicts and three conflicts between social classes. Second, conflict of wong cilik in novel Pengakuan Pariyem there are seven conflicts of wong cilik devided into six personal conflicts and one conflict between social classes. Third, the difference of wong cilik’s conflict ini novel Pengakuan Pariyem: (a) the number of conflicts, (b) wong cilik’s conflict in novel Bila Malam Bertambah Malam comes from external factors, and (c) wong cilik’s conflict in novel Pengakuan Pariyem comes from internal factors; the similarities of wong cilik’s conflict in novel Bila Malam Bertambah Malam by Putu Wijaya and Pengakuan Pariyem is found on those novel’s conflict, novel Bila Malam Bertambah Malam by Putu Wijaya is a hypogram from novel Pengakuan Pariyem by Linus Suryadi AG. Keywords: representative, conflict, wong cilik, intertextual.